2019
DOI: 10.4067/s0034-98872019000600709
|View full text |Cite
|
Sign up to set email alerts
|

Embarazo en hemodiálisis crónica: experiencia de un hospital universitario

Abstract: Background: Pregnancies in women with end stage renal failure are uncommon. However, correction of anemia and improvement in dialysis techniques increases the rate of successful pregnancies. Aim: To describe a 16 years' experience treating pregnant women on hemodialysis and to analyze maternal-fetal outcomes. Materials and Methods: Observational study of a dialysis center historical cohort in a university hospital, between 2001 and 2016. Results: Thirteen pregnancies were found in 11 women aged 23 to 32 years,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
(111 reference statements)
0
1
0
1
Order By: Relevance
“…During the selection process, 422 duplicates and 6776 references that did not agree with the research question were eliminated after reading the title and abstract (first phase). After reading the full text of the 12 preselected references, the eligibility of six of them was confirmed, [16][17][18][19][20][21] and six references were excluded for not meeting the eligibility criteria [22][23][24][25][26][27] (Table S2). The flowchart of the study selection process is shown in Figure 1.…”
Section: Search Resultsmentioning
confidence: 99%
“…During the selection process, 422 duplicates and 6776 references that did not agree with the research question were eliminated after reading the title and abstract (first phase). After reading the full text of the 12 preselected references, the eligibility of six of them was confirmed, [16][17][18][19][20][21] and six references were excluded for not meeting the eligibility criteria [22][23][24][25][26][27] (Table S2). The flowchart of the study selection process is shown in Figure 1.…”
Section: Search Resultsmentioning
confidence: 99%
“…Середня неонатальна госпіталізація склала 4 дні. Отже, вагітність під час лікування діалізом більше не є винятком, а збільшення тривалості діалізу з 23 тижня вагітності до 24 год/тиждень дозволяє істотно покращити наслідки для матері і плода [13].…”
unclassified